Atividade física na gestação e desfechos de saúde materno-infantil: Coorte de Nascimentos de 2015. - Silva, Shana Ginar da (2017)
During the last years, a growing interest in the potential beneficial effects of physical activity during pregnancy for both mother and offspring has emerged. Early studies on this topic focused on possible harm to maternal and fetal health. However, these assumptions have not been proven over time. Despite the positive evidence and evolution of the guidelines to promote physical activity in pregnancy, prior studies have shown that low levels of physical activity during pregnancy compared to those non-pregnant women. In addition, the effect of physical activity on pre-eclampsia and birth weight is still unclear. It is important to investigate patterns and correlates associated to physical activity during pregnancy for planning interventions and public polices in prenatal care. Thus, this dissertation was designed with a combination of an observational component including a description of the pattern and correlates related to physical activity measured by an objective method and an experimental component related to a randomized controlled trial (RCT) nested in the 2015 Pelotas (Brazil) birth cohort study. This dissertation also included a systematic review and meta-analysis on the effect of physical activity during pregnancy on maternal-child health. The meta-analysis of RCTs indicated that participation in leisure-time physical activity (LTPA) was associated with lower weight gain during pregnancy, lower likelihood of gestational diabetes mellitus, and lower likelihood of delivering a largefor-gestational-age infant. Cohort studies confirmed the results for gestational weight gain and gestational diabetes, and it showed a lower risk of preterm delivery. In the second paper, we showed low levels of physical activity Pregnant women spent on average 15 and 0.7 minutes a day in moderate to vigorous physical activities (MVPA) and in vigorous activity, respectively. Important differences were found regarding correlates. In the third paper, we evaluated the effect of a supervised exercise-based intervention performed during 16 weeks of pregnancy on maternal-child health. The main finding of this study was that exercise program does not present any adverse impact on newborn health such as preterm birth and low birth weight. Our study did not confirm the positive effects of exercise during pregnancy on gestational weight gain, gestational diabetes and pre-eclampsia. In summary, the findings of this dissertation provide important evidence regarding the pattern and determinants of physical activity performed during pregnancy, as well as evidence that the exercise does not negatively impact on newborn health.